Tinjauan Akad Muamalah dalam Pelaksanaan Transaksi Pre-Order: Studi Kasus HIMMPRO Ekonomi Syari’ah Febi Iuqi Bogor - Ansori, Moh. Asep Zakariya; Husenudin , Abdul; Fauziah, Siti; Istiana, Nurkhopipah; Maulidi, Muhamad Padlan (As-Syirkah: Islamic Economic & Financial Journal, 2026)
The development of technology and digital trading systems has given rise to various new forms of transactions in muamalah activities, one of which is the pre-order system. This transaction practice is widely applied in economic activities, including in student organizations. This study aims to analyze the pre-order transaction practices carried out by the Islamic Economics Student Association (HIMMPRO) of the Faculty of Economics and Business (FEBI IUQI) Bogor and review its compliance with the principles of muamalah contracts from an Islamic jurisprudence perspective. This study uses a descriptive qualitative method with a case study approach. Data collection techniques were carried out through interviews, observation, and documentation, using primary and secondary data sources. The results show that the pre-order transaction practices at HIMMPRO of Islamic Economics, FEBI IUQI Bogor, are carried out through a mechanism of ordering goods, paying a down payment (DP), the production process of goods, and settling the payment before delivery of the goods. Viewed from a muamalah jurisprudence perspective, this practice does not fulfill the provisions of the salam contract because payment is not made in full at the beginning of the contract. However, the pre-order transaction practice fulfills the pillars and requirements of the istishna contract, characterized by clear product specifications, agreed price, payment flexibility, and certainty of delivery time. Therefore, it can be concluded that the pre-order transaction practice implemented by HIMMPRO Sharia Economics FEBI IUQI Bogor is permissible (jaiz) according to sharia as long as it adheres to the principles of the istishna contract and maintains transparency and fairness in the transaction.